Analysis Of Structure And Sentence Types in The News Detik.Com Sumut 'Case of Electric Outages in Medan City' - Aulia Rahma; Yusni Khairul Amri (LingLit Journal Scientific Journal for Linguistics and Literature, 2024)
This research aims to analyze the types of sentences used in the news entitled "Case of Electric Outages in Medan City" published by detik.com Sumut. The analysis was carried out using Indonesian syntactic theory. The focus of this research is to identify the types of sentences used in the news and understand how sentence structure can influence the delivery of information to readers. This research also aims to analyze various types of sentences in Indonesian from a syntactic perspective. This study involves the identification and classification of sentences. Apart from that, this research also explores the syntactic elements that form sentences, such as subject, predicate, object, complement, and information. Through qualitative descriptive analysis, data was obtained from the news article "Case of Electric Outages in Medan City" published by detik.com Sumut. The research results show a rich variety of sentence structures in Indonesian, as well as contextual use and depending on communicative function. Based on the data above, the structure and types of sentences are: declarative sentences, imperative sentences, news/informative sentences, complex sentences, explanatory sentences, and action sentences. sentence elements. There are various sentence patterns, namely SP, SPO and SPOK sentence patterns. Types of sentences include sentences according to their function, clauses, completeness of elements, composition of subjects and predicates.